Strategi Pengelolaan Zakat Pada Lembaga Amil Zakat Di Tinjau Dari Perspektif Hukum Positif Dan Hukum Islam (Studi Kasus Di Lembaga Amil Zakat Gema Indonesia Sejahtera) - Anhar Muhamad Soleh; Irvan Iswandi (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study is motivated by the activities which undertaken by the Gema Indonesia Sejahtera Amil Zakat Institute in managing zakat and shodaqoh funds from muzakki. The aim of this study was to find out the views of positive law and Islamic law on the Zakat Management Strategy at Amil Zakat Institutions (Case Study at Amil Zakat Institution of Gema Indonesia Sejahtera). The research method used by researcher was qualitative and quantitative approach and also a type of field research. The data collection techniques used in this study were observations, interviews, and conducting studies in natural situations. Dealing with the finding, the researcher gained the following results: the activities carried out by the Gema Indonesia Sejahtera Amil Zakat Institution could assist people in need in accordance with Islamic law and positive law in force in Indonesia.